Assessing the impact of fiscal policy on poverty - Andrew McKay (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Fiscal policy measures are a key means by which governments can influence distribution and poverty, but in fact the relationships between fiscal policy and poverty are not well understood. The most commonly used technique for assessing the distributional impact, benefit incidence analysis, is straightforward, but applied by itself it suffers from a number of serious limitations. Assessment of the impact of fiscal policy needs to be developed in various directions, including allowing for behavioural responses and incorporating a broader range of information. In parallel with this careful attention needs to be paid to more effective monitoring of the poverty impsact of fiscal policy. – poverty ; fiscal policy ; benefit incidence analysis ; behavioural responses ; poverty monitoring
Keywords: H22; H30; I30; O23; 330; Armut; Einkommensverteilung; Finanzpolitik; Wirkungsanalyse